Analisis silase limbah sayur Pasar Grosir Ngronggo terhadap kapasitas tampung ternak ruminansia di Kota Kediri - Dianingtyas, Brilian Desca; Rahmawati, Nurina (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
The Ngronggo Wholesale Market in Kediri City generates predominantly organic waste, primarily vegetable waste. The development of ruminant livestock for urban farming in Kediri City is highly dependent on the land's carrying capacity, which has the potential to serve as forage for animal feed. Utilizing processed market vegetable waste as silage for ruminant livestock is one alternative to address this issue. This research aims to determine the capacity of ruminant livestock to utilize the vegetable waste silage. The research design used was a qualitative descriptive design, collecting data on the amount of vegetable waste, the number of livestock, and livestock capacity. The potential availability of vegetable waste silage from the Ngronggo Wholesale Market in Kediri City in 2024 is estimated to be 11,186.56 kg DM/year (Dry Matter/year), 378.11 kg CP/year (Crude Protein/year), and 8,423.48 kg TDN/year (Total Digestible Nutrients/year). Consequently, the potential of the vegetable waste silage from the Ngronggo Wholesale Market in Kediri City can fulfill the needs of 2,983.08 Animal Units (AU) based on DM availability, or 840.24 AU based on CP availability, or 3,743.77 AU based on TDN availability. This research concludes that silage made from vegetable waste from the Ngronggo Wholesale Market is sufficient to supply over 50% of the total animal units in Kediri City.